Aire Disruption Influences the Medullary Thymic Epithelial Cell Transcriptome and Interaction With Thymocytes - Speck-Hernandez, Cesar A.; Assis, Amanda F.; Felicio, Rafaela F.; Cotrim-Sousa, Larissa; Pezzi, Nicole; Lopes, Gabriel S.; Bombonato-Prado, Karina F.; Giuliatti, Silvana; Passos, Geraldo A. (Frontiers in Immunology, 2018)
The function of medullary thymic epithelial cells (mTECs) is associated with thymocyte adhesion, which is crucial for the negative selection of autoreactive thymocytes in the thymus. This process represents the root of central tolerance of self-components and prevents the onset of autoimmune diseases. Since thymic epithelia correspond to an important target of donor T cells during the onset of chronic graft-versus-host-disease, mTEC-thymocyte adhesion may have implications for alloimmunity. The Aire and Fezf2 genes function as transcriptome controllers in mTECs. The central question of this study is whether there is a mutual relationship between mTEC-thymocyte adhesion and the control of the mTEC transcriptome and whether Aire is involved in this process. Here, we show that in vitro mTEC-thymocyte adhesion causes transcriptome changes in mTECs and upregulates the transcriptional expression of Aire and Fezf2, as well as cell-adhesion related genes such as Cd80 or Tcf7, among others. Crispr-Cas9-mediated Aire gene disruption demonstrated that this gene plays a role in the process of mTEC-thymocyte adhesion. Consistent with the nuclear localization signal (NLS) encoded by Aire exon 3, which was targeted, we demonstrate that Aire KO-/- mTECs impair AIRE protein localization in the nucleus. Consequently, the loss of function of Aire reduced the ability of these cells to adhere to thymocytes. Their transcriptomes differed from their wild-type Aire+/+ counterparts, even during thymocyte adhesion. A set of mRNA isoforms that encode proteins involved in cell adhesion were also modulated during this process. This demonstrates that both thymocyte interactions and Aire influence transcriptome profiling of mTEC cells.